Product Prices, Service Quality, Promotion Affect Decisions on Purchasing Motorcycle Parts - Purnama Yanti Purba; Andi Andi; Tania Pratiwi; Jhas Jensen; Ade Irwansyah (International Journal of Social Science and Business, 2020)
This research was motivated by the high number of customer complaints in 2019, higher prices compared to competitors, and the lack of sales targets in the last few months. This research aimed to analyze the effect of price, service quality, and promotion on motorcycle spare parts purchasing decisions. This type of research was a quantitative descriptive study. The population in this research were 1890 customers who purchased genuine Honda spare parts at PT Indako Trading Coy. Sampling using simple random sampling technique, in order to obtain a sample of 237 people. Data collection using a questionnaire method. The data were analyzed using multiple linear regression tests. The results of the research and data analysis showed that partially the product price, service quality, and promotion have a significant influence on the decision to purchase motorcycle spare parts. Hypothesis testing shows that Fcount> Ftable (75.204> 2.64) with a significance of 0.000 <0.05. Based on this, it can be concluded that price, service quality and promotion have a positive and significant effect simultaneously on the decision to purchase motorcycle parts.